2018
DOI: 10.3390/ma11122520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Implants Coated with Radiation-Crosslinked Collagen on Stability and Osseointegration in Rat Tibia

Abstract: This study aimed to evaluate the titanium (Ti) implants coated with collagen type I crosslinked using gamma-irrigation or glutaraldehyde (GA). The in vitro surface observations, quantification assay, and cell studies using human mesenchymal stem cells (hMSCs) were conducted. For in vivo experiments, the implants were divided into three groups and inserted into the rat tibias: control group (non-treated Ti implant), GA group (Ti implants coated with GA-crosslinked collagen) and 25 kGy group (Ti implants coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…In particular, the key protein for bone tissue formation, the osteocalcin was already produced and released to be bound to ECM for mineralization. Also, the vasculogenesis process was carried out by cell-Myth (Maipek Manufacturer Industrial Care, Naples, Italy) devices, even if in a later stage with respect to the control [45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the key protein for bone tissue formation, the osteocalcin was already produced and released to be bound to ECM for mineralization. Also, the vasculogenesis process was carried out by cell-Myth (Maipek Manufacturer Industrial Care, Naples, Italy) devices, even if in a later stage with respect to the control [45][46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Schliephake et al studied collagen-coated implants and demonstrated an increase in the percentage of BIC in a dog model [29]. Also, the study of Bae (2018) [30] in a rat tibia model showed an enhancement in the osseointegration and bone healing with collagen type I crosslinked by gamma irradiation. In this research we have not investigated what happens to the collagen during the phases of osseointegration; it is probably resorbed during the phases of bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the turns of the dental implant with different dimensions, number and pitch may be affected. Coils may be present or not [30,31,32,33,34,35,36,37,38,39,40]. The function of the loops is to efficiently distribute the masticatory load and to guarantee stability in the early post-surgical phases of the implant [41,42,43].…”
Section: Methodsmentioning
confidence: 99%